2021
DOI: 10.3390/d13050216
|View full text |Cite
|
Sign up to set email alerts
|

Revisited Molecular Phylogeny of the Genus Sphaerotheca (Anura: Dicroglossidae): The Biogeographic Status of Northernmost Populations and Further Taxonomic Changes

Abstract: Heretofore, the populations of the genus Sphaerotheca Günther, 1859 (Dicroglossidae) in their northern and western borders laying in Pakistan have been assigned to two species, S. breviceps (Schneider, 1799) and S. strachani (Murray, 1884). The genus has origin in the Oriental zoogeographic region and comes to close geographic proximity with the Palearctic region in Pakistan. The recent molecular studies have on one hand restricted the distribution range of S. breviceps to the eastern coastal plains of India a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…However, genetic distance between S. pashchima and S. breviceps was 6.4% (TablesS5 and S6). Our results are in congruent with successive studies ofPadhye et al (2017),Jablonski et al (2021), andKhatiwada et al (2021), and we believe the presence of S. maskeyi (synonym:S.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…However, genetic distance between S. pashchima and S. breviceps was 6.4% (TablesS5 and S6). Our results are in congruent with successive studies ofPadhye et al (2017),Jablonski et al (2021), andKhatiwada et al (2021), and we believe the presence of S. maskeyi (synonym:S.…”
supporting
confidence: 94%
“…( 2020 ) on genus Euphlyctis , Jablonski et al. ( 2021 ) on genus Sphaerotheca, and Hofmann et al. ( 2021 ) on genus Allopaa .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there exist no recent observations on Pelophylax from Pakistan and only four exact localities are historically known with only two corroborated by available voucher specimens, it is difficult to evaluate if Pelophylax is currently a member of the herpetofauna of the country. According to Masroor (2012), Sarwar et al (2016), Frost (2021 and Jablonski et al (2021), 20 to 24 species of amphibians are currently reported from the country, without any mention of the family Ranidae or the genus Pelophylax. Pakistani Balochistan is herpetologically the most diverse region of the country (Khan 2006), yet the predominantly arid conditions do not generally provide suitable and stable habitats for amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is a country in the transition zone between the Palearctic and Oriental faunas, which is based on the fact that representatives of (not only) amphibians from both these two zoogeographic regions may be found in the country (Khan 2006;Jablonski et al 2020Jablonski et al , 2021. Currently, the territory of Pakistan contains four families of amphibians: Bufonidae Gray, 1825; Dicroglossidae Anderson, 1871;Megophryidae Bonaparte, 1850;andMicrohylidae Günther, 1858 (Masroor 2012;Sarwar et al 2016;Frost 2021).…”
Section: Introductionmentioning
confidence: 99%